Understanding Gen Z Purchase Decisions: The Roles of Lifestyle and Reference Group Influence - Aribyan, Mochamad Bintang; Susilowati, Christin (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
The objective of this research is to analyze the effects of lifestyle and reference group on people’s decision to purchase goods via Kick Avenue, an e-commerce business, by focusing on the Gen Z students of Faculty of Economics and Business, Universitas Brawijaya. The data of this quantitative study was harvested via questionnaires distributed to 150 respondents and was analyzed through multiple linear regression with t-test to identify the influence of each variable. This study finds that lifestyle positively and significantly affects the purchase decision, in which individuals’ preferences in living their life determine products and services they choose. Further, reference group also has positive and significant impacts on the purchase decision, indicating that views and behaviors within certain social groups affect consumer preferences. Additionally, lifestyle and reference group simultaneously pose significant impacts on the purchase decision, with lifestyle being the dominant variable. This study provides insights for e-commerce companies regarding how to design marketing strategies relevant with the lifestyle and the social influence of their customers.